Analysing Appreciating and Criticizing in Standard Arabic: When Morphology Supports Syntax - Alshamari, Murdhy; Albalwi, Abdulaziz (International Journal of Language and Literary Studies, 2021)
This paper provides a minimalist (Chomsky 2000, 2001) investigation to a syntactic phenomenon slightly analysed in syntactic research on Standard Arabic (SA) literature of poetry (TaqiAldin 1987). This syntactic phenomenon is derived by a construction of a wh-in situ phrase embedded in a construct state phrase (WICS, henceforth). The novelty about this SA WICS phenomenon is that the entity expressed by the wh-phrase is ambiguously assigned two pragmatic values: med? (appreciating) and hid?a? (criticizing). Holding in abeyance with the idea that SA is frozen, having not developed for decades, this research sets a comparative exploration between SA and Saudi variety of Arabic (SDA). It is shown that SDA syntax-pragmatics interface is straightforward. SDA displays WICS, which derives hid?a?, in addition to displaying wh-ex situ phenomenon, which derives med?. In comparison, SA syntax is restricted to WICS phenomenon, which predicts that in construct state context, SA only derives hid?a?, hence, the ambiguity. With minimalist investigation to further articulated structure in the SA data under analysis, the research concludes that the instance of SA WICS is an occurrence of med?, rather than hid?a?. Evidence for this conclusion is based on the observation that, though the occurrence of SA WICS is associated with lack of movement of the wh-phrase, it is simultaneously associated with a wide-scope of the discourse marker wa, which functions as a pragmatic device assigning speaker positive attitude pragmatic value to the proposition. That is to say, SA grammar requires morphology to support syntax with a morphological device when the latter falls short to activate syntactic operations like movement for med? interpretation.